Peran dan Kompetensi Auditor pada BPRS Bahari Berkesan dan BPRS Bobato Lestari - Panigfat, Nursanti (Universitas Islam Islam Sumatera Utara, 2024)
This research aims to examine the role and competence of auditors at BPRS Bahari Berkesan and BPRS Bobato Lestari. This research is qualitative research with a comparative descriptive method. Data collection techniques use observation, interviews, documentation, and literature study. The results of this research indicate that the role of internal audit carried out by BPRS Bahari Berkesan and BPRS Bobato Lestari is in accordance with the regulations issued by the Financial Services Authority (OJK) and the internal audit competency of BPRS Bahari Berkesan and BPRS Bobato Lestari must fulfill several factors that determnine competency. An auditor, namely education, training, experience, independence and professionalism to carry out supervisory duties related to financial reports so as to support compliance at BPRS. Apart from that, an internal auditor must also have an auditor can act honestly and firmly in disclosing all audit evidence according to the actual situation